Online Media and Political Power: Case on National Mandate Party in Local News - Pratama, Ferly; Damayanti, Poppi; Emzinetri, Emzinetri (UIN Fatmawati Sukarno Bengkulu, 2022)
The 2019 election in Bengkulu city has ended, but it does not require that there may be aspects that need to be observed and studied scientifically, especially how the involvement of online media is to the popularity of a party, so this study seeks to analyze political news. Analysis of political news will focus on the aspect of emphasis on the whole news section by journalists and the completeness of the whole news through framing analysis of the Zhongdang Pan and Gerald M. Kosicki model. So that the formation of the political power in question can be observed in the results of an in-depth analysis of the strengths or weaknesses of the news management party about the Bengkulu City DPW PAN on Guidelinesbenngkulu.com; (1) Journalists put emphasis on the title, source credibility, photos and graphics, although the emphasis on photos and graphics is not too much. (2) completeness of the whole news; there are still many news sections that have not described the how section so that it seems shallow; there are some parts of the news paragraph that are not in accordance with the background information; all news does not include the location of the interview; the entire news section from the title, lead, content, to the closing of the news, is in accordance with the completeness of the overall news. All political news about the Bengkulu City DPW National Mandate Party is categorized as opinion news.